365 Tumor treating fields (TTFields, 150 kHz) concurrent with standard of care treatment for stage 4 non-small cell lung cancer (NSCLC) in phase 3 LUNAR Study. (9th November 2020) - Leal, Ticiana; Bueno, Raphael; Havel, Libor; Ward, Jeffrey
Abstract : Background: Tumor Treating Fields (TTFields) are a non-invasive, anti-mitotic treatment that disrupts the formation of the mitotic spindle and dislocation of intracellular constituents. TTFields plus temozolomide significantly extended survival in newly diagnosed glioblastoma. Efficacy of TTFields in NSCLC has been shown in preclinical models as well as safety in combination with pemetrexed in a pilot study. In the Phase 3 LUNAR study [NCT02973789 ], we investigated if the addition of TTFields to immune checkpoint inhibitors or docetaxel increases overall survival (OS). Methods: Patients (N=534), with squamous or non-squamous NSCLC, are stratified by their selected standard therapy (immune checkpoint inhibitors or docetaxel), histology and geographical region. Key inclusion criteria are disease progression, ECOG 0-2, no electronic medical devices in the upper torso, and absence of brain metastasis. TTFields (150 kHz) are applied to the upper torso for at >18 hours/day until progression in the thorax and/or liver. The primary endpoint is superiority in OS between patients treated with TTFields in combination with the standard of care treatments versus standard of care treatments alone. Key secondary endpoints compare the OS in patients treated with TTFields and docetaxel versus docetaxel alone, and patients treated with TTFields and immune checkpoint inhibitors vs those treated with immune checkpoint inhibitors alone. An exploratory analysis will test non-inferiority of TTFields with docetaxel compared to checkpoint inhibitors alone. Secondary endpoints include progression-free survival, radiological response rate, quality of life based on the EORTC QLQ C30 questionnaire. The sample size is powered to detect a HR of 0.75 in TTFields-treated patients versus control group. In March 2020, an independent Data Monitoring Committee (DMC) performed a review of the LUNAR trial data collected to that point. The DMC concluded that no unexpected safety issues could be found in patients treated with the combination of immune checkpoint inhibitors and TTFields, and recommended to continue the LUNAR study as planned. Results: N/A Conclusions: N/A Acknowledgements: N/A Trial Registration: NCT02973789 Ethics Approval: The study was approved by participating centers' Institution's Ethics Boards, .NCT02973789 Consent: Not applicable Reference: N/A